Bloomsbury and the Cinema: Practice and Theory of a New Form of Expression - Floriane Reviron (Cahiers Victoriens et Edouardiens)
Just as Bloomsbury introduced post-impressionism in Great Britain, the cinema was beginning to emerge as a new art, introducing new visual vocabularies and perceptions. Our aim is to analyse Bloomsbury’s ethics and aesthetics in relation with the new issues raised by the technology of the moving pictures and the cross-fertilization between the terminology created by Bloomsbury and avant-garde film criticism. Bloomsbury’s own practice of film criticism was informed by formalism and abstraction and attests to a confluence between pictorial post-impressionism and cinematic expressionism.